Impact of Social Media Use on Transfers Knowledge on High School Teachers in Bima District with Network Ties, Shared Vision, Trust as Mediation Variables - Wahyu Ramadhana; Siswoyo Haryono; Arni Surwanti (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the impact of using social media on knowledge sharing for high school teachers in Bima Regency, with social capital represented by variables, namely network ties, shared vision and trust as mediating variables. To test the hypothesis, the researcher used data collected through questionnaires with a total of 237 respondents using purposive and convenience techniques sampling and statistical analysis, using Structural Equation Modeling (SEM) and assisted by the AMOS program. The results of the study reveal: (1) there is a positive and significant effect of social media use on network Ties and shared vision, while the social media use does not have a significant effect on the trust of high school teachers in Bima, (2) there is a positive and significant effect of network Ties and shared vision on knowledge transfer, while trust has no significant effect on knowledge transfer of high school teachers in Bima District (3) there is a positive and significant influence of social media use on knowledge transfer of high school teachers in Bima District. For the mediation test, the researcher used the Sobel test to test the indirect effect. These findings show that the network Ties and shared vision variables are able to mediate between the use of social media and knowledge transfer, while trust cannot mediate between social media use against knowledge transfer.